Retrospective Evaluation and Comparison of All Medicolegal Autopsies Performed Before and After the COVID-19 Pandemic in İzmir - Ferhat Turgut Tunçez; Gözde Yeşiltepe; Uğur Karabulut; Mehmet Tokdemir (Adli Tıp Bülteni, 2023)

(untitled)
Objective:In this study, in the 2 year period before and after the first date of the COVID-19 case in Turkey (between 11.03.2019-10.03.2020-11.03.2020-10.03.2021) İzmir Forensic Medicine Group Presidency we aimed to show the effects of the SARS-CoV-2 pandemic by examining the autopsies and autopsy findings performed in the Izmir Forensic Medicine Group Presidency through the forensic autopsy records.Methods:Our study was planned as a retrospective study of autopsies performed in İzmir Forensic Medicine Group Presidency. The work will start after the necessary permissions are obtained from the İstanbul Forensic Medicine Institute. The data of autopsies performed between 11.03.2019-10.03.2020 and 11.03.2020-10.03.2021 in the İzmir Forensic Medicine Group Presidency will be analyzed in terms of age, gender, cause of death, origin of death and mode of death.Results:A total of 4604 autopsy cases were examined in our study. In the pre-pandemic period, the number of female cases was 472 (21.4%), the number of male cases was 1734 (78.6%), the most common form of death was suspicious death with 1192 (54%), and the most common origin was 1039 (47.1%) was detected as natural death. After the pandemic, these numbers were found to be 413 (17.2%) for women, 1985 (82.8%) for men, 1398 (58.3) suspicious deaths and 1072 (44.7%) natural deaths.Conclusion:As in all areas of life, changes have occurred in forensic autopsy practice with the COVID-19 pandemic, and we think it is important to share the data we have obtained as a result of examining and analyzing all forensic autopsies performed during and before the SARS-CoV-2 pandemic in Izmir for two years.